(untitled) (Research, Society and Development, 2020)
This research aimed to analyze the relationship between spirituality at work and the perception of job well-being of workers in a city in the countryside of Rio Grande do Sul (RS). The sample consisted of 302 workers, of both sexes, belonging to organizations located in the city of Santa Maria (RS). For this, it used a research of a descriptive nature and with a quantitative approach. As for data collection, a research protocol with closed items was used, divided into three parts: Part I - Sociodemographic data; Part II - Inventory of Spirituality at Work, proposed by Siqueira (2014); and, Part III - Inventory of Well-being at Work, by Siqueira (2014). In view of the observed results, it appears that all the proposed objectives were achieved, thus answering the central question of the research. It is possible to highlight that regarding the dimensions of the constructs, it appears that work with a purpose of life and a sense of community, of spirituality at work, correlated in a moderate and positive intensity with commitment and satisfaction, of Well-being at Work, demonstrating that the more the dimensions of Spirituality at work stand out, the greater the positive relationships with commitment and satisfaction.